Pengaruh Mathematical Habits of Mind Peserta Didik terhadap Kemampuan Berpikir Kritis Ditinjau dari Gender - Yuliany, Nur; Ramadhani, Sri Ayu Amalia; Tayeb, Thamrin; Suharti, Suharti; Kusumayanti, Andi (Faculty of Tarbiyah and Teacher Training, 2025)
Mathematical habits of mind and critical thinking skills are essential in mathematics learning; however, they often differ between male and female students. This study aims to describe students’ mathematical habits of mind and critical thinking skills based on gender, as well as to analyze the influence of mathematical habits of mind on critical thinking skills. This research employed an ex post facto design with a quantitative approach, conducted at SMP Negeri 2 Pattallassang with a population of 207 eighth-grade students. A total of 136 students were selected as the sample using a simple random sampling technique. The instruments used were a questionnaire to measure mathematical habits of mind and a test to assess critical thinking skills, while data were analyzed using descriptive statistics and simple linear regression. The results showed that female students demonstrated better mathematical habits of mind and critical thinking skills compared to male students. Furthermore, mathematical habits of mind significantly influenced critical thinking skills with a determination coefficient (R Square) of 0,595, indicating that 59,5% of critical thinking skills were effected by mathematical habits of mind, while the remaining 40,5% were influenced by other factors. This study concludes that developing mathematical habits of mind is crucial for improving students’ critical thinking skills. The implication is that teachers can integrate mathematical habits of mind as a key focus in mathematics learning strategies to optimize students’ critical thinking.